Investigating the Impact of Chronic Diseases and Disability on Quality of Life in Saudi Arabian Patients - Asdaq, Syed Mohammed Basheeruddin (Asian Journal of Pharmaceutics (AJP), 2024)
Background and Objective: With greater life expectancy comes an increased risk of chronic diseases, which can lead to disability. This study aimed to investigate the relationship between chronic diseases and the development of disability, as well as their impact on quality of life (QoL). Methods: From March to May of 2024, a crosssectional survey was conducted in Riyadh, Saudi Arabia. Participants in the study were approached in a range of locations, such as disability centres, hospitals, health clinics, community gatherings, charity events, and health camps. The participants were given link to online questionnaires supplied via Google Forms. With SPSS-IBM 2023, the descriptive analysis was carried out. A significance level of P < 0.05 was applied to all comparisons. A binary regression analysis was done to determine factors that influence the QoL of the participants, while a multinomial regression analysis was carried out to explore factors that triggered the difficulty due to disability. Results: Of the 394 study participants, 70.8% were female and represented a range of age categories. Thirty-seven percent of the participants held a degree or higher education, and more than half of them—54 percent—were married. Compared to individuals without a disability, people with mild or severe disabilities are 2.355 times more likely to report a decline in QoL. There is a considerable chance that participants’ quality of life will decline when the number of chronic diseases rises from one to two or more. The quality of life (QoL) significantly improved 1.943 times among married individuals compared to those who lived alone. Growing older is linked to notable shifts in attaining a high quality of life. In general, women suffered from higher levels of disability than men did; people with good quality of life and physical activity were less likely to have higher disability indices. Conclusion: According to the study’s findings, the number of chronic illnesses and the onset of difficulty are related, and both considerably lower quality of life. Stabilizing quality of life, preventing disability, and managing chronic diseases all require effective processes involving patients, family members, and healthcare providers.